Viva o cinema e a arte literária na formação interdisciplinar de professores/as - Domingos, Hêlena Paula (2016)
The confluence of globalization and the revolution of technology sets a new ecosystem of languages and writing that is contemporary. The eletronic visuality is a constitutive part of cultural visibility. This research investigates the insertion of the media cinema in the educational field using an interdisciplinary approach with teacher training and the context of these educators in mind, through a multi perspectivistic approach. It is set by the following problem: How the media cinema contributes to a critical reading of reality? How the methodological corpus of analysis selects the movies Frankenstein (2004), by Mary Shelley (1797-1851) and "1984" (1984), resulted from the literary work with the same name by George Orwell (1903-1950). It seeks theoretical framework and methodology in the axiological field of Cultural Studies, in the basis of action research and the ways of addressing, which film analysis centers in the cultural production, to the visual text itself and its reception, by the public. This investigation considers the teachers training as a possibility of question the media cinema and its pedagogical interdisciplinary perspective.